LIFE EVENTS WITH STRESSFUL EFFECT ON PATIENTS WITH SCHIZOPHRENIA ACCORDING TO THE SEX AND AGE. - Lilia Nikolova; Rinaldo Shishkov; Мila Georgieva (Peytchinski Publishing, 2012)
According to the literature life events with stressful effect are significant both for initiation and progress of the schizophrenia. Having this in mind we set our aim to be investigating the relationship between life events (considered as stressful), sex and age trough questioning 50 patients with paranoid schizophrenia. The results of our study showed presence of correlation between some of the studied life events, assessed as stressful. The analysis of the data revealed that both sex and age are influencing the assessment of the significance of the life events and "increases" their importance both for women and men.